(untitled) (Bangladesh Journal of Botany, 2025)
Five commercial varieties of Trichosanthes anguina were studied cytogenetically for authentic characterization based on heterochromatic distribution pattern. The interphase nuclei of the variety Apurbo showed diffuse type of interphase nuclei, staining with homogenous distribution of chromatin in orcein staining. Complex chromocenter type with big heteropycnotic blocks were observed in the interphase nuclei of the rest four varieties namely, Turag, Dhaka green, Super long green and Anika. The prophase chromosomes of the variety Turag, Anika and Apurbo were homogeneously stained whereas these gradually stained in Dhaka green variety. The interstitial region of prophase chromosomes of Super long green were stained in orcein. These five varieties displayed distinction in GC-rich repeats distribution in interphase and prophase stage of mitotic cell division. Therefore, with the help of cytogenetical analysis, it was possible to characterize each variety based on its heterochromatin distribution pattern by differential staining. Bangladesh J. Bot. 54(1): 49-52, 2025 (March)